분리하중에 대한 항공기용 외부연료탱크 구조 건전성 평가 - 김현기(Hyun-gi Kim); 김성찬(Sungchan Kim); 박민수(Min-su Park); 안수홍(Su-hong An) (항공우주시스템공학회지, 2024)
The external fuel tank of an aircraft is a main component that can increase the cruising range of the aircraft. It must be able to be stably separated from the pylon in an emergency situation. At this time, a separation load is applied to the fin and the pivot of the external fuel tank. To stably separate the external fuel tank, the structural soundness of the fin and the pivot must be confirmed. In this study, structural tests were conducted to verify the structural integrity of the external fuel tank pin and pivot when the external fuel tank was separated from the aircraft. Results are then presented. In this paper, a test configuration diagram consisting of the hydraulic and load control equipment, data acquisition system, and pneumatic supply unit used in the structural test was explained. Test installation and test load application plan for each test condition were provided. As results of the structural test, it was found that test load and internal pressure of the test specimen were properly controlled within the allowable range in each test. It was confirmed that serious structural defects in the test specimen did not occur under required load conditions. In conclusion, through structural test for design limit load and design ultimate load, it was proven that the fin and pivot of the external fuel tank for aircraft covered in this study had sufficient structural strength. 항공기 외부연료탱크는 항공기의 항속거리를 증가시키는 주요 구성품으로써, 비상시 파일런에서 안정적으로 분리될 수 있어야 된다. 이 때, 외부연료탱크의 핀(fin)과 피벗(pivot)에는 분리하중이 작용하게 되는데, 외부연료탱크의 안정적인 분리를 위해서는 핀과 피벗의 구조 건전성이 입증되어야 한다. 본 연구에서는 항공기로부터 외부연료탱크가 분리 될 때 외부연료탱크의 핀과 피벗의 구조건전성 검증을 위해 수행된 구조시험 결과를 제시하였다. 본문에서는 구조시험에 사용되는 유압 및 하중제어장비, 데이터 획득장치 그리고 공압공급장치로 구성되는 시험구성도를 설명하였고, 각 시험조건에 대한 시험설치와 시험하중 인가계획을 제시하였다. 구조시험 결과, 각 시험조건에서 시험하중과 시험체의 내부압력이 허용 범위 내에서 적절히 제어되는 것으로 파악되었고, 시험체에서도 심각한 구조적 결함이 발생하지 않았음이 확인되었다. 최종적으로, 설계 제한하중과 설계 극한하중에 대한 구조시험을 통해서 본 연구의 항공기용 외부연료탱크 핀과 피벗은 충분한 구조 강도를 보유하고 있음을 확인하였다.